2019
DOI: 10.2217/fon-2019-0479
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Mass Risk Assessment: A Multivariate Index Assay for Malignancy Risk Stratification

Abstract: Aims: Adnexal mass risk assessment (AMRA) stratifies patients with adnexal masses, identifying the relatively small number of malignancies from benigns which might take a ‘watchful waiting’ approach. Methods: AMRA uses seven biomarkers and derived from women with adnexal masses scheduled for surgery. Estimated clinical performance was calculated using fixed prevalence. Results: At 5% prevalence, the high-risk group, 7.9% total, captured 75.9% of invasive malignancies at a positive predictive value of 35.8%. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Of note, the predictive values were quite balanced due to the disease prevalence that was 51.5% (123/239) in the first cohort and 57.1% (20/35) in the second independent cohort. This balanced prevalence, as expected [ 31 ], enhances the role of the DSS in predicting the risk of malignancy allowing to strongly reduce both false positives and false negatives. We would also specify that all patients enrolled in the study underwent surgery for various reasons: suspicion of malignancy on ultrasound, patient request, symptoms worsening the quality of life, reasons connected with fertility.…”
Section: Discussionsupporting
confidence: 62%
“…Of note, the predictive values were quite balanced due to the disease prevalence that was 51.5% (123/239) in the first cohort and 57.1% (20/35) in the second independent cohort. This balanced prevalence, as expected [ 31 ], enhances the role of the DSS in predicting the risk of malignancy allowing to strongly reduce both false positives and false negatives. We would also specify that all patients enrolled in the study underwent surgery for various reasons: suspicion of malignancy on ultrasound, patient request, symptoms worsening the quality of life, reasons connected with fertility.…”
Section: Discussionsupporting
confidence: 62%
“…The previous site collections were done according to five different protocols, including OVA1-001-CO1, OVA2-002-CO3, OVA1-7788, OVA1-PS1-CO4, and RP 01-2016. The purpose of each collection has previously been reported [6][7][8][9]. Each site independently obtained Institutional Review Board approval.…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian cancer is the fifth highest cause of cancer related deaths among women [ 1 , 2 ]. An estimated 5–10% of women will develop an adnexal mass during their lifetime [ 3 ]. Surgical intervention is a common treatment option, yet studies have shown that only 10% of the 200,000 patients in the USA who undergo surgery for an adnexal mass annually are found to have ovarian cancer [ 4 ].…”
mentioning
confidence: 99%